Perilaku Mahasiswa dalam Menggunakan ChatGPT dalam Menunjang Proses Pembelajaran di Program Studi Perpustakaan dan Ilmu Informasi - Putri, Rosi; Marlini, Marlini (Lembaga Yasin AlSys, 2025)
This research aims to explore student behavior in using ChatGPT as a tool in the learning process at the Library and Information Science Study Program at Padang State University. The background to this research focuses on the gap in understanding and use of AI technology in education, especially among students. The method used is a quantitative approach by collecting data through questionnaires distributed to 54 students class of 2022. The research results show that students have a good understanding of using ChatGPT, but there are challenges in reading quotes, extracting information. The conclusion of this research states that even though students utilize ChatGPT, improvements are still needed in several aspects to optimize the use of this technology in learning.